Analysis of Sulfur Dioxide (SO2) Exhaust Gas Emission Distribution Patterns from Airport’s Incinerators in East Java - Adhi Pamungkas, Kresna Setyawan; Restu Hikmah Ayu Murti; Muhammad Abdus Salam Jawwad (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
The airport in this study is one of the airports in East Java that uses an incinerator to process its waste. Emissions generated by the incinerator will disperse in the area surrounding one of the airports in East Java. With the increasing interest of the public in air travel, activity at the airport also increases. This increase also impacts the amount of waste processed by the incinerator and the emissions produced, including Sulfur Dioxide (SO2). The aim of this study is to analyze the dispersion of air pollutants using Aermod View modeling software with SO2 parameters from environmental document data of the airport from January to June and from July to December generated by the incinerator stack. The model produces isopleths representing the dispersion of SO2 emissions. The results of the SO2 model still meet ambient air quality standards, as indicated in Appendix VII of Government Regulation Number 22 of 2021.